Optimization of macronutrients for improved grain yield of quinoa (Chenopodium quinoa Wild.) crop under semi-arid conditions of Morocco - Taaime, Nawal; El Mejahed, Khalil; Choukr-Allah, Redouane; Bouabid, Rachid; Oukarroum, Abdallah; El Gharous, Mohamed (Frontiers in Plant Science, 2023)
In the context of climate change, quinoa represents a potential alternative crop for increasing crops diversity, agricultural productivity, and farmer’s income in semi-arid regions. However, appropriate crop management practices under limited water supply are still poorly documented. Quinoa, like other cultivated crops, needs optimum quantities of nutrients, especially nitrogen (N), phosphorus (P), and potassium (K), for better growth and high grain yield. To determine the adequate levels of nutrient requirements and their effect on quinoa growth and productivity, a field experiment was conducted during two growing seasons (2020–2021 and 2021–2022). The experiment was conducted in Ben Guerir region, north-central Morocco, and consisted of a randomized complete block design (RCBD) with three replications. The treatments studied consist of a combination of four N rates (0, 40, 80, and 120 kg ha−1), three P rates (0, 30, and 60 kg P2O5 ha−1), and three K rates (0, 60, and 120 kg K2O ha−1). The physiological, nutritional, and production parameters of quinoa were collected and analyzed. The results showed that the highest total biomass (3.9 t ha−1) and grain yield (0.8 t ha−1) under semi-arid conditions were obtained with 40 kg N ha−1, 60 kg P2O5 ha−1, and 120 kg K2O ha−1. The application of 40–60–120 kg ha−1 of N–P2O5–K2O increased plant height by 44%, chlorophyll content index by 96%, total biomass by 134%, grain yield by 112%, and seed weight by 118%. Among the three macronutrients, N was the most limiting factor, followed by K and P. Nutrients uptake data showed that quinoa needs 60 kg N, 26 kg P2O5, and 205 kg K2O to produce 1 t of grain yield. Our field results provide future recommendations for improving the agronomic and environmental sustainability of quinoa cultivation in dryland areas in Morocco.